Lo misional en pedagogía - Marín Cabrero, Rosa (Revista Española de Pedagogía, 2019)
Missionary work, which includes the missioner, his activity, the mission in itself and missionary doctrine, taken in its catholic sense and from a pedagogical point of view, presents certain analogies on one side, since missionary work, when it aims to the salvation of souls, has teaching as one of its principal natural means; on the other side it reveals the pedagogical contributions of missioners, which have not yet properly studied, and also the educational value of missionary ideal especially on children and young people. The authoress, after finding out these relationships, points out the one which has arisen from the educational problemes in missionary countries and which now demands a missionary Pedagogy within the field of differential Pedagogy.
Keywords: misional; pedagogía; Revista Española de Pedagogía